Incidencia de los proyectos escolares en el fomento de la investigación estudiantil en el Colegio Manuel Gonzalo Albán Rumazo de la parroquia Aláquez del cantón Latacunga - Casnanzuela Jaque, Martha Cecilia (2015)
The following research work has as a goal to encourage a research culture among students through school projects at "Manuel Gonzalo Praise Rumazo" school of Aláquez Parish in Latacunga Canton. This research was conducted by a survey technique which allowed to analyze the results, identifying the lack of new strategies that encourage students to generate a creative and dynamic research, leaving behind the simple mechanism repetition. Furthermore, this research helped to present a proposal in which teachers used this research as a means to improve the teaching-learning process as well as the assimilation of knowledge in a practical way, which all are immersed in the new educational processes. Within the proposal, it has developed a training workshop focused on the teachers as facilitators who work on each school projects. It will be a positive and viable initiative to implant the investigation, so it is recommended that the educative institution executes the proposal made so that the school projects will be the base in order to foment the research.